2022
DOI: 10.1016/j.eclinm.2021.101253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protection by COVID-19 vaccines after deployment in low and lower-middle income countries

Abstract: The availability and use of vaccines for the coronavirus disease 2019 (COVID-19) in low and middle-income countries (L/MICs) lags far behind more affluent countries, and vaccines currently used in L/MICs are predominantly of lower efficacy. As vaccines continue to be rolled out in L/MICs, successful control of COVID-19 by vaccines requires monitoring both of vaccine protection of vaccinees (effectiveness) and of the entire targeted populations, including vaccine herd protection of non-vaccinees (impact). To be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…All vaccines used in the COVID-19 Vaccination Program in Angola had reported efficacy in phase 3 clinical trials superior to that recommended by the WHO (Logunov et al, 2021;World Health Organization, 2021a, 2021b, 2021c. The difference found in the general VE of our study with those published previously may be due to the fact that the phase 3 clinical trials in which the VE used in Angola were determined do not consider relevant factors present in the real world, such as the expansion of the range recipients of vaccines beyond those eligible for testing initially, administration of vaccine with incomplete or mixed regimens, variation of dosing intervals, possibility of storage and incorrect administration of vaccines, concomitant administration with other drugs by vaccinates that are not permitted for participants in phase 3 trial, the decline in vaccine immunity over time and the emergence of new genetic variants of SARS-CoV-2 with protein targets not initially considered in the manufacture of currently available vaccines such as Omicron (Clemens et al, 2022). This last question seems to us to be the most relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All vaccines used in the COVID-19 Vaccination Program in Angola had reported efficacy in phase 3 clinical trials superior to that recommended by the WHO (Logunov et al, 2021;World Health Organization, 2021a, 2021b, 2021c. The difference found in the general VE of our study with those published previously may be due to the fact that the phase 3 clinical trials in which the VE used in Angola were determined do not consider relevant factors present in the real world, such as the expansion of the range recipients of vaccines beyond those eligible for testing initially, administration of vaccine with incomplete or mixed regimens, variation of dosing intervals, possibility of storage and incorrect administration of vaccines, concomitant administration with other drugs by vaccinates that are not permitted for participants in phase 3 trial, the decline in vaccine immunity over time and the emergence of new genetic variants of SARS-CoV-2 with protein targets not initially considered in the manufacture of currently available vaccines such as Omicron (Clemens et al, 2022). This last question seems to us to be the most relevant.…”
Section: Discussionmentioning
confidence: 99%
“…A review study on "Evaluation of protection by COVID-19 vaccines after deployment in low-and middle-income countries" published in late December last year identified 58 published studies that included 85 evaluations of the effectiveness of different COVID-19 vaccines in Worldwide. In this study, only three had been carried out in low-and middleincome countries, and no impact studies were identified in these settings (Clemens et al, 2022). Also in March 2021, The World Health Organization (WHO) has issued guidelines for the design and conduct of non-randomized vaccine protection efficacy studies for vaccines used in low-and middle-income countries on the basis that there is a divergence in vaccine protection that can occur when vaccines are deployed in public health practice compared to measurement in individually randomized, designed, phase 3 efficacy trials for licensing, because such trials do not take into account all the pertinent vaccine protection issues encountered in a lifetime public health setting real.…”
Section: Justificationmentioning
confidence: 99%
“…A review study on "Evaluation of protection by COVID-19 vaccines after deployment in low-and middle-income countries" published in late December last year identified 58 published studies that included 85 evaluations of the effectiveness of different COVID-19 vaccines in Worldwide. In this study, only three had been carried out in low-and middle-income countries, and no impact studies were identified in these settings (Clemens et al, 2022). Also in March 2021, The World Health Organization (WHO) has issued guidelines for the design and conduct of non-randomized vaccine protection efficacy studies for vaccines used in low-and middle-income countries on the basis that there is a divergence in vaccine protection that can occur when vaccines are deployed in public health practice compared to measurement in individually randomized, designed, phase 3 efficacy trials for licensing, because such trials do not take into account all the pertinent vaccine protection issues encountered in a lifetime public health setting real.…”
Section: Justificationmentioning
confidence: 99%
“…All vaccines used in the COVID-19 Vaccination Program in Angola had reported efficacy in phase 3 clinical trials superior to that recommended by the WHO(Logunov et al, 2021; World Health Organization, 2021a, 2021b, 2021c, 2022. The difference found in the general VE of our study with those published previously may be due to the fact that the phase 3 clinical trials in which the VE used in Angola were determined do not consider relevant factors present in the real world, such as the expansion of the range recipients of vaccines beyond those eligible for testing initially, administration of vaccine with incomplete or mixed regimens, variation of dosing intervals, possibility of storage and incorrect administration of vaccines, concomitant administration with other drugs by vaccinates that are not permitted for participants in phase 3 trial, the decline in vaccine immunity over time and the emergence of new genetic variants of SARS-CoV-2 with protein targets not initially considered in the manufacture of currently available vaccines such as Omicron(Clemens et al, 2022). This last question seems to us to be the most relevant.…”
mentioning
confidence: 99%
“…By the end of the year of 2021, the pandemic had claimed the life of about 18 million people worldwide [8]. Effective vaccines were only widely deployed in 2021, with a delayed distribution in underdeveloped countries [9,10]. The transmission of SARS-CoV-2 is mainly airborne, with a relatively high estimated ratio of transmissions originated from asymptomatic or presymptomatic infected people [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%